Detection of Intracranial Hemorrhage from Computed Tomography Images: The Diagnostic Role and Efficacy of ChatGPT-4o - Koyun, Mustafa; Cevval, Zeycan Kubra; Reis, Bahadir; Ece, Bunyamin (MDPI AG, 2024)
Background/Objectives: The role of artificial intelligence (AI) in radiological image analysis is rapidly evolving. This study evaluates the diagnostic performance of Chat Generative Pre-trained Transformer (ChatGPT) in detecting intracranial hemorrhages (ICH) on non-contrast computed tomography (NCCT) images, along with its ability to classify hemorrhage type, stage, anatomical location, and associated findings. Methods: A retrospective study was conducted using 240 cases, comprising 120 ICH cases and 120 controls with normal findings. Five consecutive NCCT slices per case were selected by radiologists and analyzed by ChatGPT-4o using a standardized prompt with nine questions. Diagnostic accuracy, sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) were calculated by comparing the model’s results with radiologists’ assessments (gold standard). After a two-week interval, the same dataset was re-evaluated to assess intra-observer reliability and consistency. Results: ChatGPT-4o achieved 100% accuracy in identifying imaging modality type. For ICH detection, the model demonstrated 68.3% diagnostic accuracy, sensitivity of 79.2%, specificity of 57.5%, PPV of 65.1%, and NPV of 73.4%. It correctly classified 34.0% of hemorrhage types and 7.3% of localizations. All ICH-positive cases were identified as acute phase (100%). In the second evaluation, diagnostic accuracy improved to 73.3%, with sensitivity of 86.7% and specificity of 60%. The Cohen’s Kappa coefficient for intraobserver agreement in ICH detection indicated moderate agreement (κ=0.469). Conclusions: ChatGPT-4o shows promise in identifying imaging modalities and ICH presence but demonstrates limitations in localization and hemorrhage type classification. These findings highlight its potential for improvement through targeted training for medical applications.
Keywords: Medicine (General); ChatGPT; R5-920; computed tomography; artificial intelligence; intracranial hemorrhage; radiology; Article